Dysregulated hyaluronan metabolism drives inflammation and angiogenesis in proliferative diabetic retinopathy - Abu El-Asrar, Ahmed M.; Nawaz, Mohd I.; Ahmad, Ajmal; Siddiquei, Mairaj; Allegaert, Eef; Gikandi, Priscilla W.; De Hertogh, Gert; Opdenakker, Ghislain (Frontiers in Immunology, 2026)
PurposeTo investigate the expression levels of enzymes and receptors of the hyaluronan (HA) pathway, including HA synthase (HAS)-2, hyaluronidase (Hyal)-1, Hyal-2, CD44 and receptor for HA-mediated motility (RHAMM) in the ocular microenvironment of patients with proliferative diabetic retinopathy (PDR) and the role of HA pathway in inflammation and angiogenesis that drive PDR initiation and progression.MethodsEpiretinal fibrovascular membranes from PDR patients, vitreous samples from PDR and nondiabetic patients, rat retinas, retinal Müller glial cells and human retinal microvascular endothelial cells (HRMECs) were studied by immunohistochemistry, ELISA, Western blot analysis and spectrofluorometric analysis. Functional studies included evaluation of in vivo blood-retinal barrier integrity and analysis of in vitro cell adhesion and angiogenesis.ResultsHA, HAS2, Hyal-1, Hyal-2, CD44, syndecan-1 and heparan sulphate levels were upregulated in PDR vitreous samples. Immunohistochemical analysis revealed expression of HAS2, Hyal-2, CD44 and RHAMM in epiretinal membranes, with significant positive correlations between angiogenic activity and HAS2, Hyal-2 and CD44 expression. Diabetes upregulated Hyal-1, CD44, RHAMM and reactive oxygen species in rat retinas. Intravitreal administration of ultralow molecular weight HA (ULMW-HA) in normal adult rats increased retinal vascular permeability and induced upregulation of phospho-NF-κB, phospho-ERK1/2, VEGF, HMGB1, ICAM-1 and VCAM-1 protein levels. In Müller cell cultures, ULMW-HA induced upregulation of phospho-ERK1/2, phospho-NF-κB, HMGB1, VEGF, angiopoietin-2 and MCP-1/CCL2 proteins. The ERK1/2 inhibitor U-0126 and the NF-κB inhibitor BAY11–7085 attenuated ULMW-HA–induced upregulation of VEGF, angiopoietin-2 and MCP-1/CCL2 levels. The hyaluronidase inhibitor apigenin reduced the levels of VEGF and MCP-1/CCL2 induced by diabetic mimetic conditions. In cultured HRMECs, ULMW-HA induced cell migration, whereas apigenin attenuated shedding of soluble syndecan-1 induced by diabetic mimetic conditions and reduced TNF-α–induced upregulation of ICAM-1, VCAM-1 and adherence of monocytes.ConclusionsAbnormal HA metabolism is involved in diabetes-induced retinal endothelial dysfunction and ULMW-HA drives inflammation and angiogenesis in PDR.